Efeito da temperatura de intercamada e da adição de arame frio em manufatura aditiva por deposição a arco em aço carbono - Lopes, Gustavo de Castro (2023)
Additive Manufacturing by Arc Deposition (ADM) consists in the manufacture of metallic preforms from the deposition of multilayer weld beads on a substrate, that is, from a three dimensional model, the object is divided into layers defining the trajectories in which the addition of metal will be made, with the use of a robotic manipulator. This method has advantages such as a high deposition rate and the possibility of manufacturing parts of large proportions, compared with other methods. However it still requires studies to consolidate the technique and potential for improvement and development of new procedures, such as filling strategies and cooling processes between deposited layers. The objective of this work is to study the influence of the addition of cold wire in the MADA process, comparing it with the deposition made with a single wire, observing mechanical properties such as tensile strength, hardness, in addition to the cooling time for different interpass temperatures and the geometry of the manufactured parts. A GMAW (Gas Metal Arc Welding) system was used coupled to a Motoman HP20 robotic manipulator, with multiple wires of 1.6 mm in diameter for the energized wire and 1.0 mm for the cold wire, both classified as ER70S-6. The feed speed of the cold and energized wires was 1.5 m/min and 3.0 m/min, respectively. To measure the temperature, an MLX90614ESF-DCI sensor was used, connected to an Arduino system. In addition, a mixture of Argon with 25% of Carbon dioxide was used as a shielding gas with a flow rate of 25 L/min. In order to manufacture the specimens for the tensile test, 20 layers were superimposed in a straight line, forming a wall, varying the interpass temperature between each layer, using 100ºC, 150ºC and directly, with no waiting interval between layers. The walls were made, later it was production of specimens for tensile tests was carried out, using a CNC machining center. In the preparation of the bodies for hardness tests, the same methodology was followed, followed by the sanding and polishing process. In general, a shorter cooling time was observed for the walls manufactured with the addition of cold wire when compared to depositions with a single wire. In addition, it was noted that the cold wire also influences the height and thickness of the pieces. In the mechanical tests, the cold wire did not significantly influence the hardness values. The highest values were found in the 100ºC samples. For the tensile tests, it was observed that, in general, the addition of cold wire tended to increase the maximum tensile strength of the samples.